Inhibition of UVB-mediated Oxidative Stress in Immortalized HaCaT Keratinocytes by n-hexane Terpenoid Rich Canarium odontophyllum Extract (TRCO) as Evinced by Markers of Photodamage - Ahmad Rohi, Ghazali; Yogabaanu, Ulaganathan; Muhammad Wahizul Haswan, Abdul Aziz; Dayang Fredalina, Basri (UNIMAS Publisher, 2024)
Acute exposure of eukaryotic cells to ultraviolet-B (UVB) radiation leads to a number of detrimental effects, one such prominent effect of UVB exposure is increased production of free radicals which can lead to oxidative damage. Although, the human skin is well equipped with endogenous antioxidant defence system, often increased levels of free radicals lead to oxidative damage in skin. Skin inflammation, accelerated skin aging, and formation of wrinkles are all consequences of UVB induced photodamage. Hence, it is posited that supplementation of an exogenous antioxidant derived from natural products could prevent and reduce oxidative damage in skin cells. This study set forth to investigate the antioxidative role of terpenoid rich Canarium odontophyllum Miq. (Dabai) extract on acute UVB-induced photodamage human keratinocyte cells (HaCaT). We first evaluated the antioxidative capacity of increasing concentrations of crude extracts of TRCO Dabai extracts (62.50 μg/mL, 125 μg/mL, 250 μg/mL, and 500 μg/mL) through FRAP assay. We found all the tested TRCO extract exhibited antioxidative capacity in dosage dependent manner. We further investigated the effects of pre-treatment 250 μg/mL and 500 μg/mL TRCO on UVB-induced photodamaged HaCaT cell by measuring oxidative stress markers of lipid peroxide (LPO content), protein carbonyl (PC) content, glutathione peroxidase (GSH-Px) and glutathione-S-transferase (GST) activities. Both 250 μg/mL and 500 μg/mL TRCO extract pre-treated UVB-induced HaCaT cell group exhibited significantly reduced lipid peroxides content and GST activity compared to the positive control (p<0.05). Pre-treatment of 250 μg/mL TRCO extract significant enhanced GSH-Px activity (p<0.05). However, no significant difference in protein carbonyl content could be established across all tested groups. Therefore, our results suggest that TRCO extract can offer protection against oxidative damages caused by UVB exposure, and said protective effects can be attributed by its antioxidant properties.